Overturning protection control of lunar-planetary lander with semi-active shock absorber - Takao MAEDA; Masatsugu OTSUKI; Tatsuaki HASHIMOTO (Nihon Kikai Gakkai ronbunshu, 2014)
This paper describes the attitude control method for overturning prevention for a lunar planetary lander which uses a semi-active damper on the landing leg. In order to achieve safe landing on uneven terrain especially a sloped ground, a novel landing gear system is required. The landing leg with variable damping is one of the solutions for touchdown without overturning. Conventional landing gear for lunar and planetary lander has a fixed shock attenuation parameter and it is not used proactively for attitude control of the lander in the touchdown sequence. By controlling the damping coefficient of the each landing leg, it becomes possible to suppress the disturbance on the attitude of the lander, and it prevents overturning. First, the strategies for the overturn prevention for the lander by changing damping coefficient of landing legs are shown and the control rules based on the lander and landing leg state values are proposed. In the second place, the mathematical model of lander based on the differential algebraic equation in vertical two-dimensional plane is presented. Besides footpad-ground contact model is also described. Finally, touchdown simulations on a sloped terrain with the proposed landing gear control method are shown. Numerical simulations show that the proposed landing gear system works well during the touchdown on a sloped terrain.